上顎小臼歯部に生じた腺性歯原性囊胞の1例 - 稲垣, 友里; 田沼, 順一; 住友, 伸一郎; 永山, 元彦; 田中, 四郎; 金子, 裕康 (日本口腔外科学会雑誌, 2018)
Glandular odontogenic cysts are odontogenic developmental cysts that commonly arise in the mandible. Their frequency of onset in the maxilla is low. We report a glandular odontogenic cyst arising in the maxillary premolar region. The patient was a 36-year-old man who was examined at our department because of swelling of the gum as the main complaint. At the first examination, swelling with pulsation was observed in the maxillary canine and first premolar gum regions. However, the maxillary canine and first premolar showed vital reactions when an electric pulp tester was used. Computed tomography revealed bone absorption with buccal cortical bone loss in a well-defined area, 10 mm in diameter, including the maxillary canine and first premolar regions. However, there was no communication between the region of bone loss and the apex. As a maxillary bone cyst was suspected, cystectomy was performed with the patient under local anesthesia. During surgery, detachment of the cyst was achieved easily, and after the excision, the surrounding bone surface was smoothened. A hemostatic splint was placed on the open wound. The patient was given a diagnosis of a glandular odontogenic cyst based on the histopathological findings of the excised specimen. The patient’s progress continues to be positive, with no recurrence as of 2 years 3 months after surgery.